2017
DOI: 10.1097/qad.0000000000001278
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum albumin and aspartate transaminase with 5-year all-cause mortality in HIV/hepatitis C virus coinfection and HIV monoinfection

Abstract: Objective Liver disease markers have been associated with mortality in HIV-infected individuals, in the modern era of effective antiretroviral therapy. Our objective was to determine which markers are most predictive of mortality in HIV-monoinfected and HIV/HCV-coinfected persons. Research Design and Methods We measured serum albumin, total protein, calculated globulin, aspartate transaminase (AST), and alanine transaminase (ALT) in 193 HIV/HCV-coinfected and 720 HIV-monoinfected persons in the study of Fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…Our study found that an elevated gamma gap demonstrated a high specificity for HIV, which is consistent with HIV's effect on humoral immunity resulting in hypergammaglobulinemia [23][24][25]. However, the gamma gap generated by hypergammaglobulinemia is affected by severity of HIV per CD4 count and viral load [26] and its treatment status [25,27,28], which may explain the higher prevalence ratios at lower gamma gap thresholds as well as the poor sensitivity of elevated gamma gap for HIV. Prior studies have shown that regardless of treatment status and viremic level, those with HIV exhibit more intense staining at the gamma region of the serum electrophoresis, represented by antibodies such as IgG and IgA, than those without HIV [27,29], resulting in hypergammaglobulinemia.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our study found that an elevated gamma gap demonstrated a high specificity for HIV, which is consistent with HIV's effect on humoral immunity resulting in hypergammaglobulinemia [23][24][25]. However, the gamma gap generated by hypergammaglobulinemia is affected by severity of HIV per CD4 count and viral load [26] and its treatment status [25,27,28], which may explain the higher prevalence ratios at lower gamma gap thresholds as well as the poor sensitivity of elevated gamma gap for HIV. Prior studies have shown that regardless of treatment status and viremic level, those with HIV exhibit more intense staining at the gamma region of the serum electrophoresis, represented by antibodies such as IgG and IgA, than those without HIV [27,29], resulting in hypergammaglobulinemia.…”
Section: Discussionsupporting
confidence: 78%
“…Similar to HIV, the gamma gap demonstrated a high specificity for HCV infection. The mechanism for this specificity could also be related to B cell activation [30,31] in addition to reduced albumin synthesis secondary to liver disease and poor nutrition [26]. Like HIV, disease severity and treatment status affect gamma gap levels and may contribute to its poor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Liver and renal diseases are the leading causes of death in HIV‐positive individuals . At the beginning of the HIV epidemic, patients with HIV infections were not considered eligible for transplantation for fear that the immunosuppressive medication would advance the HIV infection.…”
Section: Brief History Of Hiv‐positive To Hiv‐positive Transplantationmentioning
confidence: 99%
“…Liver and renal diseases are the leading causes of death in HIVpositive individuals. 4,5 At the beginning of the HIV epidemic, patients with HIV infections were not considered eligible for transplantation for fear that the immunosuppressive medication would advance the HIV infection. With advancements in immunosuppression drugs, some transplant hospitals performed kidney and liver transplants in HIV-positive individuals with uninfected deceased donor organs.…”
Section: B Rief His Tory Of Hiv-p Os Itive To Hiv-p Os Itive Tr An mentioning
confidence: 99%
“…28 As waiting lists remain very long and many USA patients can wait up to 10 years for a deceased donor kidney transplant, many patients will accept an HIV-positive organ instead of waiting on an HIVnegative organ.…”
mentioning
confidence: 99%